2022
DOI: 10.1186/s12889-022-14368-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of shielding advice on the wellbeing of individuals identified as clinically extremely vulnerable amid the COVID-19 pandemic: a mixed-methods evaluation

Abstract: Background The national shielding programme was introduced by UK Government at the beginning of the COVID-19 pandemic, with individuals identified as clinically extremely vulnerable (CEV) offered advice and support to stay at home and avoid all non-essential contact. This study aimed to explore the impact and responses of “shielding” on the health and wellbeing of CEV individuals in Southwest England during the first COVID-19 lockdown. Methods A tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…While existing work has explored the impact of the pandemic on the mental health and quality of life of SOT recipients 4 7-10 and other 'higher risk' groups, 3 5 6 few studies 2 3 have considered the impact of public health communications on such groups. Adding to research that suggests individuals found shielding advice 'impractical and restrictive', 2 this study emphasises the even more troubling feelings of fear, anxiety and 'terror' (P12) that BMJ Public Health shielding communications engendered among many SOT recipients. This has similarly been found among other 'CEV' groups.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…While existing work has explored the impact of the pandemic on the mental health and quality of life of SOT recipients 4 7-10 and other 'higher risk' groups, 3 5 6 few studies 2 3 have considered the impact of public health communications on such groups. Adding to research that suggests individuals found shielding advice 'impractical and restrictive', 2 this study emphasises the even more troubling feelings of fear, anxiety and 'terror' (P12) that BMJ Public Health shielding communications engendered among many SOT recipients. This has similarly been found among other 'CEV' groups.…”
Section: Discussionmentioning
confidence: 87%
“…Recognising the severity of the UK's shielding rules, several studies have explored the impact of shielding on the well-being and quality of life of individuals classified as CEV, [2][3][4][5][6] with some evidence to suggest that mental health worsened significantly as a result of shielding. 2 SOT recipients-the first group listed under the definition of CEV by the UK Department of Health and Social Care in March 2020 1 -are one group that has received specific attention, with several studies exploring the impact of the pandemic on the mental health and quality of life of those living with a transplant. 4 7-10 However, qualitative studies exploring the experiences of SOT recipients are lacking.…”
Section: Bmj Public Healthmentioning
confidence: 99%
“…Pregnant women who were clinically vulnerable were advised to “shield” [ 9 ]. ‘Shielding’ was a term used by the UK Government to protect people who were at the highest risk of being hospitalised by COVID-19, they were advised not to leave their homes and within their home to minimise time spent with others and to avoid using shared spaces when others were present [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…While parents were advised to ensure their children engaged in physical activity during the initial lockdown, the extent to which this occurred, and the impact of that initial period of isolation and inactivity is uncertain. Some parents and children may also have been very cautious about the risks associated with COVID-19, engaging in additional protective behaviours that were not explicitly recommended by the Government and which may have exerted an additional toll on well-being [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%